Speak-PIM, Towards a Framework for the Automatic Detection of Potentially Inappropriate Prescriptions...32nd Medical Informatics Europe Conference (MIE2022), 27-30 May, 2022, Nice, France. - MOUAZER, Abdelmalek; SEDKI, Karima; TSOPRA, Rosy; LAMY, Jean-Baptiste (Studies in Health Technology & Informatics, 2022)
Potentially inappropriate medications (PIMs) have adverse health consequences, particularly in elderly patients. Various explicit criteria have been developed to detect PIMs. However, it is difficult to apply these criteria without the help of an electronic decision support tool. Programming these tools can be very complex. Indeed, for computer scientists it is difficult to understand medical issues and for clinicians it is difficult to program in a computer programming language. In this work we present Speak-PIM, a framework for formalizing the PIM’s rules. Speak-PIM is based on a very simple semantics which is suitable for the declaration of PIMs without embarking on all the complexity of description logic or computer languages. It aims to offer an efficient collaboration between the computer scientists and clinicians.